Isolation and characterization of bacterial community from lake water for manganese removal - Jun, Noraprilenna (2020)
Water scarcity was the result of imbalance natural phenomena across the world with the combination of the irresponsible act of human towards our beautiful Earth. Most of the water supply can be obtained on the surface water. However, it is depending on the geological population where some will be obtained from groundwater. However, due to many factors largely contributed from human being, water reservoir contaminated with harmful compound especially manganese. Divalent soluble manganese can be catalysed to insoluble manganese oxide by using bacteria known as manganese oxidizing bacteria (MOB). The MOB is phylogenetically diverse and can be isolated from various sources like ocean, basalt and many more. Hence, this study will be focusing on isolation and characterization of pure culture originated from surface lake water. The pure isolation technique will be conducted to isolate the community to its single colony. The single colony next will be characterized by mostly its biological character. After being isolated, Gram Staining Test will be used to characterize the isolated bacteria based on its cell wall constituents and will be observed by using microscope. The gram-positive bacteria will have violet colour and pink for gram-negative bacteria under the microscope observation. The manganese tolerance test then conducted to test the ability of the bacteria to grow in the presence of manganese at various concentration. The number of colonies formed plotted into a graph versus manganese concentration after one day incubation period. The kinetic Growth Curve plotted within 24 hours growing in the incubator.